If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 15v = -63 Solving -3 + 15v = -63 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 15v = -63 + 3 Combine like terms: -3 + 3 = 0 0 + 15v = -63 + 3 15v = -63 + 3 Combine like terms: -63 + 3 = -60 15v = -60 Divide each side by '15'. v = -4 Simplifying v = -4
| 4x^2+31x-19=2 | | 0=500n-2000 | | 16xy+28x+12y+21= | | -9r^3(7r^2+6)(7r^2-6)=0 | | 32w+8= | | x^2=-4x-20 | | -14x-14=2x+7 | | 4x^2+20x+19=6 | | 4y^4(2y+1)(y-6)=0 | | 3v^2+20+32=0 | | x^2+5=42 | | (3a-3d)(3a+2d)=0 | | 9+x=-125 | | 7x-28-30=33 | | 49x^2-3=06 | | 3+x=-150 | | 39x^2=36 | | 5+x=230 | | (3z-u)(3z+2u)=0 | | 4(X-20)=2X+10 | | .25p+.2(10-p)=0 | | (6-u)(4+2u)=0 | | 2+x=-34 | | -93=-3+-15x | | (9x+2)(9x+2)=0 | | 0.2(1.5z-5)=4(4z+1) | | x(445-4x)=10000 | | 10n-0.375=.1n-.375 | | -30x-6=-66 | | 2x-28=-7(4+5x)+2x | | -2(x-7)=12 | | 5(y-8)-7y(y-8)=0 |